The maintenance of regional dialects: a matter of gender? Boys, but not girls, use local varieties in relation to their friends' nativeness and local identity - Barbu, Stéphanie; Martin, Nathael; Chevrot, Jean-Pierre (Frontiers in Psychology, 2014)
The linguistic diversity enduring beyond institutional pressures and social prejudices against nonstandard dialects questions the social forces influencing language maintenance across generations and how children contribute to this process. Children encounter multi-dialectal interactions in their early environment, and increasing evidence shows that the acquisition of sociolinguistic variation is not a side issue but an inherent part of the general acquisition process. Despite these recent advances in sociolinguistic acquisition, children’s sociolinguistic uses remain under-studied in relation to peer social networks and the ability to use dialect for identity purposes. Our study focused on a grammatical sociolinguistic variable consisting of the alternation between a regional and a standard variant of the third person object pronoun in French. The regional variant is a remnant of the Francoprovençal language and its usage by adults is strongly associated with local identity in the French Alps. We described, using questionnaires, the social networks of 117 10-11 year-old girls and boys living in the same restricted rural area. Thirteen native target children (7 girls and 6 boys) were selected from the sample, as well as 39 same-sex friends chosen according to their place of birth (native vs non-native) and the duration of their friendship with the targets (number of years they have known each other). The target children were recorded during spontaneous dyadic conversations during free play at school with each category of friends. Target boys, but not girls, used the regional variant significantly more frequently with their long-term native friends than with their non-native friends. This adjustment mirrored their partners’ uses. Moreover, with long-term native friends, boys used the regional variant twice as frequently as girls. Boys appeared thus as key actors in the maintenance and the diffusion of regional cues in local social networks.